2002
DOI: 10.1002/ijc.10855
|View full text |Cite
|
Sign up to set email alerts
|

Roles of JNK‐1 and p38 in selective induction of apoptosis by capsaicin in ras‐transformed human breast epithelial cells

Abstract: Efforts have been made to develop a chemoprevention strategy that selectively triggers apoptosis in malignant cancer cells. Previous studies showed that capsaicin, the major pungent ingredient of red pepper, had differential effect between normal and transformed cells. As an approach to unveil the molecular mechanism by which capsaicin selectively induces apoptosis in transformed cells, we investigated the effect of capsaicin in nontransformed and ras-transformed cells of a common origin: parental (MCF10A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 42 publications
(56 reference statements)
5
48
0
Order By: Relevance
“…In culture, capsaicin has been found to selectively suppress the growth of various human tumor cells (14,15), including leukemic (16 -18), gastric (19), hepatic (20), glioma (21), and prostate cells (9). How capsaicin mediates its anticancer effects is not fully understood, but the roles of NADH oxidase activity (14), proteasome (9), cyclooxygenases (22), c-Jun NH 2 -terminal kinase (23), nuclear factor-nB (24), peroxisome proliferator-activated receptor g (25,26), peroxynitrite (21), and mitochondrial respiration (27) have been implicated. Its immunosuppressive effects have been linked to its ability to suppress nuclear factor-nB activation (28).…”
mentioning
confidence: 99%
“…In culture, capsaicin has been found to selectively suppress the growth of various human tumor cells (14,15), including leukemic (16 -18), gastric (19), hepatic (20), glioma (21), and prostate cells (9). How capsaicin mediates its anticancer effects is not fully understood, but the roles of NADH oxidase activity (14), proteasome (9), cyclooxygenases (22), c-Jun NH 2 -terminal kinase (23), nuclear factor-nB (24), peroxisome proliferator-activated receptor g (25,26), peroxynitrite (21), and mitochondrial respiration (27) have been implicated. Its immunosuppressive effects have been linked to its ability to suppress nuclear factor-nB activation (28).…”
mentioning
confidence: 99%
“…Metastasis, a characteristic of highly malignant cancers with poor clinical outcome, is one of the major causes of mortality in breast cancer patients. Therefore, anti-tumor agents that may inhibit invasion and migration of breast cancer cells have been extensively pursued in many laboratories, including ours (35,36). Although many studies have reported the anti-tumor activity of genipin in various cancer cells, there is a limited amount of information on the anti-invasive activity of genipin.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in procaspase-3 cleavage was observed during CPS-induced apoptosis of human hepatocarcinoma cells, 34 and increased caspase-3 activity occurred in the CPS-induced apoptosis of H-Ras-transformed breast epithelial cells. 55 Moreover, the caspase-3 inhibitor (Ac-DEVD-cmk) blocked DNA fragmentation in Jurkat cells exposed to vanilloid phorbol 12-phenylacetate 13 acetate 20-homovanillate.…”
Section: 51mentioning
confidence: 96%